👤

solve the following:

1. (3x+ 5)(-7x-2)

2. (9m-6n)(9m+6n)


3. (3a + 4b)³​


Sagot :

Answer:

1.) -21x²-41x-10

2.)81m²-36n²

3.)27a³+108a²b+144ab²+64b³

Answer:

2. (9m-6n)(9m+6n)

step 1: square the first term

(9m)²=81m²

step 2:square the product of first and the second term

2(9m)(-6n)=-108mn

step 3:square the last term

(-6n)²=36n²

81m²-108mn+36n² but the case is unlike sign the middle will be remove the answer is 81m²-36n² 3. (3a + 4b)³= (3a+4b) (3a+4b) (3a+4b)

= (3a)³+ 3(3a)²(4b)+3(3a)(4b)²(4b)²

= 27a³+108ab+144ab+64b³

sorry i don't know the answer in no.1